(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Nigeria is among the countries that have experienced many building collapses, raising concerns about the quality of building materials and the necessity of examining their suitability for construction. Sandcrete blocks are essential for building construction and are used in the masonry unit for walling and other purposes. There is a growing concern about the proliferation of sandcrete production industries in various locations and the need to ascertain their standards. The present paper assessed the quality of sandcrete blocks produced in Benin City, Edo State, for compliance with existing standards. Sandcrete blocks produced in selected block industries in the Benin Metropolis, Edo State factories were used in the study. Ninety (90) nine-inch hollow Sandcrete blocks were collected from sixteen (18) block industries in the Benin metropolis, with five (5) blocks collected from each factory. The processes and techniques engaged among manufacturers, including batching, curing, mix proportion, age of block, and quality assurance, were observed. The block samples were subjected to laboratory experimentation to test the standard specifications compared to the established standard specifications in Nigeria. The outcomes of the laboratory tests revealed that the sampled blocks' size, compressive strength, and water absorption capacity fell short of the required standards. The key findings of the field survey revealed deviations from the standards in the mix proportioning, curing procedures, and age of the blocks used in the industries.